Newborns with Bloody Stools-At the Crossroad between Efficient Management of Necrotizing Enterocolitis and Antibiotic Stewardship - Marie Heyne-Pietschmann; Dirk Lehnick; Johannes Spalinger; Franziska Righini-Grunder; Michael Buettcher; Markus Lehner; Martin Stocker (MDPI AG, 2021)
The onset of bloody stools in neonates often results in antibiotic treatment for suspected necrotizing enterocolitis (NEC). Food protein-induced allergic proctocolitis (FPIAP) is an often-neglected differential diagnosis. We performed a retrospective analysis of antibiotic exposure at our tertiary center from 2011 to 2020 that included three time periods of differing antimicrobial stewardship goals. We compared these data with the conventional treatment guidelines (modified Bell's criteria). In our cohort of 102 neonates with bloody stools, the length of antibiotic exposure was significantly reduced from a median of 4 to 2 days. The proportion of treated neonates decreased from 100% to 55% without an increase in negative outcomes. There were 434 antibiotic days. Following a management strategy according to modified Bell's criteria would have led to at least 780 antibiotic days. The delayed initiation of antibiotic treatment was observed in 7 of 102 cases (6.9%). No proven NEC case was missed. Mortality was 3.9%. In conclusion, with FPIAP as a differential diagnosis of NEC, an observational management strategy in neonates with bloody stools that present in a good clinical condition seems to be justified. This may lead to a significant reduction of antibiotic exposure. Further prospective, randomized trials are needed to prove the safety of this observational approach.